Effects of BRCA2 deficiency on telomere recombination in non-ALT and ALT cells - Sapir, Ester (BioMed Central, 2011)
BACKGROUND: Recent studies suggest that BRCA2 affects telomere maintenance. Interestingly, anti cancer treatments that involve BRCA2 and telomerase individually are currently being explored. In the light of the above recent studies their combinatorial targeting may be justified in the development of future treatments. In order to investigate effects of BRCA2 that can be explored for this combinatorial targeting we focused on the analysis of recombination rates at telomeres by monitoring T-SCEs (Telomere Sister Chromatid Exchanges). RESULTS: We observed a significant increase in T-SCE frequencies in four BRCA2 defective human cell lines thus suggesting that BRCA2 suppresses recombination at telomeres. To test this hypothesis further we analyzed T-SCE frequencies in a set of Chinese hamster cell lines with or without functional BRCA2. Our results indicate that introduction of functional BRCA2 normalizes frequencies of T-SCEs thus supporting the notion that BRCA2 suppresses recombination at telomeres. Given that ALT (Alternative Lengthening of Telomeres) positive cells maintain telomeres by recombination we investigated the effect of BRCA2 depletion in these cells. Our results show that this depletion causes a dramatic reduction in T-SCE frequencies in ALT positive cells, but not in non-ALT cells. CONCLUSION: BRCA2 suppresses recombination at telomeres in cells that maintain them by conventional mechanisms. Furthermore, BRCA2 depletion in ALT positive cells reduces high levels of T-SCEs normally found in these cells. Our results could be potentially important for refining telomerase-based anti-cancer therapies.